Ghrelin Receptor Is Required for the Effect of Nesfatin-1 on Glucose Metabolism - Fan, Xin-Tong; Tian, Zhao; Li, Shi-Zhen; Zhai, Ting; Liu, Jun-Li; Wang, Rui; Zhang, Cai-Shun; Wang, Liu-Xin; Yuan, Jun-Hua; Zhou, Yu; Dong, Jing (Frontiers in Endocrinology, 2018)
Studies of nesfatin-1 in glucose metabolism have become a topic of interest recently, however, the specific receptor for nesfatin-1 has not yet been identified. Some studies hinted at a connection between nesfatin-1 and the ghrelin receptor, growth hormone secretagogue receptor (GHSR). Therefore, we aimed to study the role of GHSR in the glycemic effects of nesfatin-1 as well as its downstream pathways. We employed C57/BL6 mice (wild type and GHSR knockout mice) eating a normal chow diet and a high fat diet in this study, and the experimental technique included western blot, real-time PCR, immunofluorescence and ELISA. We found that in mice fed a normal chow diet (NCD), nesfatin-1 improved glucose tolerance, up-regulated AKT kinase (AKT) mRNA levels and phosphorylation and GLUT4 membrane translocation in skeletal muscle. These effects were blocked by co-injection of GHSR antagonist [D-Lys3]-GHRP-6 and were attenuated in GHSR knockout mice. In mice fed high-fat diet (HFD), nesfatin-1 not only exerted the effects observed in NCD mice, but also suppressed appetite and raised AKT levels in liver tissues that also required GHSR. Peripheral nesfatin-1 suppressed c-fos expression of GHSR immunoreactive neurons induced by fasting in hypothalamic nuclei, indicating that nesfatin-1 inhibited the activation of central GHSR. We concluded that the effects of nesfatin-1 on food intake and glucose metabolism were GHSR-dependent, and that the glycemic effect was associated with AKT and GLUT4. This study should stimulate further exploration of the nesfatin-1 receptor.